The influence of european revolutionary movements of 1918 – 1920’S. for the development ideas of european integration - Skripnik, Olena (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract Introduction. In this article to analyzes the development of revolutionary movements in Europe after First World War. This period was characterized by a significant revolutionary upsurge caused a revolution in Russia. Revolution took place in Germany, Hungary, Czechoslovakia, Poland, Ukraine, and Finland, the peoplesrevolted in France, Great Britain and Italy. Also, the rise of the national liberation movement observed in the colonies and dependent countries. All revolutionary movements of the early twentieth century had mixed consequences for countriesand for international relations as a whole. But we note that at this time, a arise number of ideas, which contributed to the future of European integration, and the impact of the emergence of these ideas were too revolutionary movements that took place in Europe. Purpose. The aim is to explore and analyze the features of the influence of European revolutionary movements of the early twentieth century to the development and formation of the idea of European integration. Results. With the proclamation of the Republic of Austria, in November 1918 the famous Austrian politician and scholar R. Coudenhove-Kalergiclearly creates and promotes the idea of supranational political alliances and the concept of European unity. In the early 20’s. he pointed to the great danger intra hatred of what can happen on a new world war. It is necessary tonoted that the European integration idea has significant influence and revolution in Russia. Originality. To investigated the idea of European integration T. Masaryk, namely the idea of forming a "United States of Eastern Europe." To determined the features of the emergence of pan-European Union. Conclusion. As a result of World War I, the collapse of the Russian, Austro-Hungarian, Ottoman, German empires, aggravation of social problems and disappointment in the existing power structures – Europe has seized a powerful revolutionary movement. Great influence on the revolutionary movement in Europe and had a revolution in Russia. These revolutionary developments prompted a number of leading Europeans talk about the union of European states,for the purpose of the economic recovery of Europe after the First World War,prevent a new war and particularly confrontation bolshevik progress in Europe